Reliability of bioreactance-derived hemodynamic monitoring during simulated sustained gravitational transitions induced by short-arm human centrifugation. (September 2022) - Zecca, Fabio; Nkansah, Kwasi Jr; Travers, Gavin; Araujo, Sergi Vaquer; Green, David Andrew
Highlights: Current methods of monitoring stroke volume index (SVI) in space are inappropriate. The non-invasive bioreactance-based device Starling™ SV may be a valid alternative. Short-arm centrifugation was used to simulate transitions between µg, 1 g, and 1.5 g. Precision and sensitivity of bioreactance SVI data across five gz phases were high. Evaluation of Starling™ SV against a reference method in microgravity is warranted. Abstract: Precise, sensitive, and non-invasive estimates of stroke volume index (SVI) would facilitate clinical decision making and tracking of cardiorespiratory fitness in space. Thoracic electrical bioreactance (TEBR) is capable of providing valid SVI estimates on Earth; however, its reliability in response to simulated sustained gravitational transitions is unknown. Ten healthy male subjects underwent short-arm human centrifugation (SAHC) equivalent to 1 g and 1.5 g at their center of mass along the z-axis (gz ) for 10 min each (first 5 min: passive; last 5 min: active, leg press movements), interspersed by periods without centrifugation (µg). The TEBR-based device Starling™ SV was used to estimate SVI during the five distinct passive gz phases. Precision of SVI measurements and sensitivity to hemodynamic changes induced by simulated gz transitions were determined. Overall SVI precision was very high (coefficient of variation = 3.6%), whereas mean sensitivity to SVI changes was satisfactory (sensitivity index = 75%). This study shows that the TEBR-based device Starling™ SV is precise and sensitive to hemodynamic changes in response to simulated sustained gz transitions induced by SAHC. Thus, it may be a suitable non-invasive hemodynamic monitor during human spaceflight. Further evaluation of Starling™ SV against a reference method in simulated microgravity is warranted. Graphical abstract: Image, graphical abstract